Systematic Analysis of the Aberrances and Functional Implications of Ferroptosis in Cancer - Zekun Liu; Qi Zhao; Zhixiang Zuo; Shuqiang Yuan; Kai Yu; Qingfeng Zhang; Xiao-Long Zhang; Hui Sheng; Huai‐Qiang Ju; Han Cheng; Feng Wang; Rui‐Hua Xu; et al. (2020)
Ferroptosis is a type of cell death related to cancer; however, the characteristics of ferroptosis in cancers are still uncertain. Based on the data in The Cancer Genome Atlas, we found that most ferroptosis regulator genes (FRGs) were differentially expressed in tumors, somatic copy number alterations (SCNA) and DNA methylation contributed to their aberrant expression. We established the ferroptosis potential index (FPI) to reveal the functional roles of ferroptosis and noticed that the FPI was higher in tumors than in normal tissues in most cancers and was associated with subtypes and clinical features. The FPI was negatively correlated with several metabolic pathways but positively associated with several important metastasis-related pathways and immune-related pathways. High FPI predicted poor prognosis in several tumors, whereas FPI and FRGs impacted drug sensitivity. Our study presents a systematic analysis of ferroptosis and its regulatory genes and highlights the potential of ferroptosis-based cancer therapy.